PERMUKIMAN SPONTAN DI KECAMATAN BUNGURAN TIMUR KABUPATEN NATUNA - , DEFRIZAL, Prof. Ir. Sudaryono, M. Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rapid urbanization leads to an inability of the carrying capacity of an area, and will eventually causes a variety of problems, one of which is the issu of settlements. In fact, the Natuna regency is a relatively new territory with an area of 264.198,37 km2, so it is still able to accommodate population growth in the next few years. However the problem of settlement has occurred in Natuna Regency, especially in the Bunguran Timur districts. This is proved by the settlement that is built spontaneously. This research aims to identify the character of Spontaneous settlement in Bunguran Timur districts, and to determine the causes of the appearance of the Spontaneous settlement. This research conducted in Bunguran Timur districts, Natuna Regency, because this districts is the capital districts of Natuna, and has the highest number of population. This research used a qualitative analysis of induction with the phenomenological approach which emphasizes the understanding of the ground situation, and in-depth understanding of the information from the sources about the couses of emergence of Spontaneous settlement in Bunguran Timur Districts. The research founds that there are 3 (three) characters of Spontaneous settlement in Bunguran Timur Districts, (1) squatter settlement on land the local government land, (2) settlement in the water area, (3) settlement without a permit (IMB) in their own land. Every settlements has a different character compared to others. The only similiarity that can be identified as a Spontaneous settlement is the process of the establishment by independent, and incompleteness of building permits. After the process of observe and analysis deeper, found 2 (two) general factors causing the emergence of Spontaneous settlement in Bunguran Timur districts. First, the presence of cenggang factor, namely the idea that the people donât want to know about the rules, and itâs hard to accept something new.In this case the community is hard to accept the new state that any development must be accompanied by a permit to build, so that people would not be concerned about the rule. The second factor is lost control of local government. Existence of local government in public life in Bunguran Timur Districts more embracing sense of kinship, and than impact on the governmentâs inability to implement existing regulations. Keyword : (1) Spontaneous settlement (2) causative factors